Social media: motivations for sharing tourism experiences among UiTM Terengganu students / Mohd Amir Faris Shamsudin & Norhazwani Mazwan - Shamsudin, Mohd Amir Faris; Mazwan, Norhazwani (Faculty of Hotel and Tourism, 2018)
The tourism industry has greatly benefitted from the advancement of technology such as the internet that disseminate large amount of tourism related information through a large network. It has enabled the development of social networking technologies such as social media which triggers tourists’ action towards sharing their tourism related information with other people connected to the same social network and eventually building further social relationship. However, evaluating the internet resources is not easy and the reason behind massive information sharing is still unclear. Hence, this study aims to examine the tourists’ motivation for sharing tourism experience via the social media in order to determine their pattern of sharing online content. From the study conducted, majority of the respondents hold an Instagram account (69.8%, 266 respondents) and prefer the mastery of visual content as the main medium when posting online (72.4%, 276 respondents). Approximately the mean is 4.13 of the respondents (n=381) were motivated to share their travelling experience due to keep my friends and family up to date From the research conducted, the practice of sharing information through social media appears as a norm and tourists occasionally share their travelling experience right after their trip (48.6%, 185 respondents) with their social community.